1993
DOI: 10.7326/0003-4819-119-10-199311150-00003
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithmic Approach to Chronic Cough

Abstract: A sequential approach to chronic cough that emphasizes initial treatment with an antihistamine-decongestant is effective. Bronchoprovocation challenge is useful in evaluating patients with chronic cough but can be delayed until the initial response to antihistamine-decongestant therapy has been assessed. The 18% incidence of recurrence highlights the fact that cough often is the manifestation of a chronic or recurring process that requires chronic or episodic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
3
26

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(195 citation statements)
references
References 0 publications
11
155
3
26
Order By: Relevance
“…Several prospective studies have demonstrated asthma to be among the most common causes of chronic cough (24-29%) in nonsmoking adults [6,12,50]. Usually, cough is associated with the more typical symptoms of dyspnoea and wheezing.…”
Section: Asthmatic Cough and Eosinophilic Bronchitismentioning
confidence: 99%
“…Several prospective studies have demonstrated asthma to be among the most common causes of chronic cough (24-29%) in nonsmoking adults [6,12,50]. Usually, cough is associated with the more typical symptoms of dyspnoea and wheezing.…”
Section: Asthmatic Cough and Eosinophilic Bronchitismentioning
confidence: 99%
“…In addition, nasal challenge with menthol is known to diminish cough reflex sensitivity and urge-to-cough sensation in healthy volunteers [67]. Empirical therapy with first-generation antihistamines (with or without a decongestant) has proved to be a successful approach [68], although questions remain as to whether this is due to the amelioration of the underlying disorder or to an intrinsic antitussive effect of these agents [69].…”
Section: Question 13mentioning
confidence: 99%
“…The present study indicates that PSE might be useful for patients suffering from unnecessary cough. In fact, it is reported that the use of PSE as decongestant improves chronic cough, while the newer antihistamines are ineffective (32). This may be due to the antitussive effect rather than any decongestive effect of PSE.…”
Section: Discussionmentioning
confidence: 94%